1999
DOI: 10.1002/hep.510300220
|View full text |Cite
|
Sign up to set email alerts
|

Transport of monoglucuronosyl and bisglucuronosyl bilirubin by recombinant human and rat multidrug resistance protein 2

Abstract: The secretion of bilirubin conjugates from hepatocytes into bile represents a decisive step in the prevention of hyperbilirubinemia. The bilirubin conjugates, monoglucuronosyl bilirubin (MGB) and bisglucuronosyl bilirubin (BGB), were previously suggested to be endogenous substrates for the apical multidrug resistance protein (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
97
0
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 169 publications
(105 citation statements)
references
References 38 publications
(80 reference statements)
6
97
0
2
Order By: Relevance
“…As for rMrp2, the free liver concentration of rifampicin did not reach the IC 50 value of Mrp2 (34.0 mM), which was obtained using CDCF as a typical substrate for rMrp2. Although CDCF was used as a substrate for rMrp2 in the present study, the reported IC 50 value of cyclosporin A using bilirubin monoglucuronide as an rMrp2 substrate (Kamisako et al, 1999) was almost consistent with our determined IC 50 value of cyclosporin A. In addition, inhibition studies of rifampicin for rNtcp, rBsep, and rUgt1a1 were conducted but the inhibitory effects were low.…”
Section: Biomarkers For Inhibition Of Transporterssupporting
confidence: 83%
See 1 more Smart Citation
“…As for rMrp2, the free liver concentration of rifampicin did not reach the IC 50 value of Mrp2 (34.0 mM), which was obtained using CDCF as a typical substrate for rMrp2. Although CDCF was used as a substrate for rMrp2 in the present study, the reported IC 50 value of cyclosporin A using bilirubin monoglucuronide as an rMrp2 substrate (Kamisako et al, 1999) was almost consistent with our determined IC 50 value of cyclosporin A. In addition, inhibition studies of rifampicin for rNtcp, rBsep, and rUgt1a1 were conducted but the inhibitory effects were low.…”
Section: Biomarkers For Inhibition Of Transporterssupporting
confidence: 83%
“…In hepatobiliary transporters, bilirubins are substrates of OATPs (Cui et al, 2001;Briz et al, 2003) and MRP2 (Kamisako et al, 1999), whereas bile acids are substrates of NTCP (Hagenbuch and Meier, 1994;Stieger, 2011) and BSEP (Noé et al, 2002;Stieger, 2011). Therefore, when the transporters are inhibited by exogenous substances such as drugs, it appears that plasma levels of bilirubins or bile acids are increased independently of drug-induced hepatotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…26 MRP2 mRNA levels appeared lower in PFIC livers (Table 3), but the differences did not reach significance because of considerable variation in MRP2 mRNA and protein levels (Fig. 4B).…”
Section: Resultsmentioning
confidence: 92%
“…The molecular and biochemical aspects, and clinical relevance of these transporters have been well-described in recent reviews. [146][147][148][149][150][151][152][153][154] It has been demonstrated that certain drugs are substrates for these transporters, e.g., digoxin, paclitaxel and vinblastine for MDR3 155) ; bilirubin conjugates for MRP2 156) ; anticancer drugs, and glucronide and GSH conjugates for MRP3 [157][158][159] ; cidfovir and adefovir for OAT1 160) ; methotrexate and cimetidine for OAT3 161) ; pravastatin 162,163) and methotrexate 164,165) for OATP-C (OATP2, LST-1); digoxin for OATP8 166) ; quinidine (at pH 6.0) for OCT1 167) ; amantadine for OCT2 168) ; quinidine and verapamil for OCTN1 169) ; and quinidine and verapamil for OCTN2. 170,171) It has been established that genetic polymorphisms of drug metabolizing enzymes are responsible for inter-individual differences of pharmacokinetics and thereby pharmacodynamics, however, little is known about the effects of genetic polymorphisms of membrane transporters.…”
Section: Polymorphisms Of Other Transportersmentioning
confidence: 99%